Register Now

222-9+11+12:2*14+14 = ? ( )

## Toán Lớp 8: k, (x+3)(2x-1)=(x+3)(x-2) m, x ²-4x+4=(2-x)(3x+1) Chi tiết đầy đủ hứa vote 5*

Toán Lớp 8: k, (x+3)(2x-1)=(x+3)(x-2)
m, x ²-4x+4=(2-x)(3x+1)
Chi tiết đầy đủ hứa vote 5*

1. Giải đáp + Lời giải và giải thích chi tiết:
k) $(x + 3)(2x – 1) = (x + 3)(x – 2)$
$\Leftrightarrow (x + 3)(2x – 1) – (x + 3)(x – 2) = 0$
$\Leftrightarrow (x + 3)(2x – 1 – x + 2) = 0$
$\Leftrightarrow (x + 3)(x + 1) = 0$
$\Leftrightarrow$ $$\left[ \begin{array}{l}x+3=0\\x+1=0\end{array} \right.$$
$\Leftrightarrow$ $$\left[ \begin{array}{l}x=-3\\x=-1\end{array} \right.$$
Vậy S = {-3; -1}
m) $x^2 – 4x + 4 = (2 – x)(3x + 1)$
$(x – 2)(x – 2) = (2 – x)(3x + 1)$
$(x – 2)(x – 2) = (x – 2)(-3x – 1)$
$(x – 2)(x – 2 + 3x + 1) = 0$
$(x – 2)(4x – 1) = 0$
$\Leftrightarrow$ $$\left[ \begin{array}{l}x-2=0\\4x-1=0\end{array} \right.$$
$\Leftrightarrow$ $$\left[ \begin{array}{l}x=2\\x=\dfrac{1}{4}\end{array} \right.$$
Vậy S = {2; 1/4}

2. Lời giải và giải thích chi tiết+Giải đáp:
k)
(x+3)(2x-1)=(x+3)(x-2)
<=>(x+3)(2x-1)-(x+3)(x-2)=0
<=>(x+3)(2x-1-x+2)=0
<=>(x+3)(x+1)=0
<=> $$\left[ \begin{array}{l}x+3=0\\x+1=0\end{array} \right.$$
<=>$$\left[ \begin{array}{l}x=-3\\x=-1\end{array} \right.$$
Vậy: S={-3;-1}
m)
x^2-4x+4=(2-x)(3x+1)
<=>(x-2)^2=(2-x)(3x+1)
<=>(x-2)(x-2)-(2-x)(3x+1)=0
<=>(x-2)(x-2)+(x-2)(3x+1)=0
<=>(x-2)(x-2+3x+1)=0
<=>(x-2)(4x-1)=0
<=>$$\left[ \begin{array}{l}x-2=0\\4x-1=0\end{array} \right.$$
<=>$$\left[ \begin{array}{l}x=2\\x=1/4\end{array} \right.$$
Vậy: S={2;1/4}